Morfologi Bahasa Melayu Manado - Ilke Moniung, Vany Kamu (Kajian Linguistik, 2021)
Indonesia as a country possess many local wisdoms as well as many variatyes of local languages. It has been the unvaluable richness which needs attention and prevention. Â The prevention is very valuable in the field of language maintenance in order to prevent the language vasihment in the form of written and oral. This article emphasized on the understanding of society toward the development of Manadonese Malay in the revitalization process. Morphological process of Manadonese Malay can be done by classifying the local language by using Nidaâ€™s theory.